Climate‐change impacts on ecological systems: introduction to a US assessment. Issue 9 (1st November 2013) - Grimm, Nancy B; Staudinger, Michelle D; Staudt, Amanda; Carter, Shawn L; Chapin, F Stuart; Kareiva, Peter; Ruckelshaus, Mary; Stein, Bruce A
Abstract : As part of the 2014 US National Climate Assessment, over 60 subject‐matter experts from government agencies, academia, nongovernmental organizations, and the private sector assessed the current and projected impacts of climate change on ecosystems, biodiversity, and ecosystem services. Here, we introduce and provide context for the papers included in this Special Issue, drawing upon the key findings from separate assessments of biodiversity, ecosystem structure and function, ecosystem services, climate‐change impacts in the context of other stressors, and societal responses to change (ie climate adaptation). We also explain the assessment process and show how the current state of knowledge can be used to identify risks and guide future research and management initiatives.